(untitled) (Research, Society and Development, 2021)
Canistel (Pouteria campechiana (Kunth) Baehni) is a tropical fruit with a yellow pulp due to the presence of carotenoids, which may be interesting for application by the food industry. The aim of this research was to analyze the phytochemical and technological characteristic of dehydrated canistel pulp by thermal dehydration and freeze-drying techniques. Test for antioxidant activities (DPPH and ABTS radical scavenging; ferric reducing antioxidant power - FRAP), total polyphenols, flavonoids, carotenoids content (UV-Vis, FTIR and Raman spectroscopy), color, and hygroscopic properties were performed. The freeze-dried sample showed a higher carotenoids concentration, more intense coloring and better hydration properties than the thermally dehydrated sample. Functional groups such as water, carotenoids, primary and secondary amides, aldehydes groups, phenolic acids, aromatic rings, cellulose, polysaccharides and niacin were identified by FTIR in both samples. Ingredient obtained by freeze drying showed better technological characteristics, allowing its use by the food industry.